2014
DOI: 10.1007/s00436-014-3903-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective and universal primers for trematode barcoding in freshwater snails

Abstract: Trematodes are significant pathogens of high medical, veterinary, and environmental importance. They are hard to isolate from their intermediate hosts, and their early life stages are difficult to identify morphologically. Therefore, primers were developed for trematodes to create a species barcoding system and allow selective PCR amplification in mixed samples. The specific oligonucleotide primer was universal for trematodes that infected several freshwater snail species in Israel. The diagnostic tool is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…It is also important to consider the role of bird migration in the spread of these parasites. Although there were no reports of migratory birds infected in this study, they have been reported as Paratanaisia hosts (Routtu et al 2014) and could become important carriers, spreading the parasites to locations where bird migration is common.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…It is also important to consider the role of bird migration in the spread of these parasites. Although there were no reports of migratory birds infected in this study, they have been reported as Paratanaisia hosts (Routtu et al 2014) and could become important carriers, spreading the parasites to locations where bird migration is common.…”
Section: Discussionmentioning
confidence: 64%
“…The overlap in the morphometric measures of the three species precludes an accurate morphological identification. However, the use of PCR to amplify ribosomal gene fragments and sequencing the products should allow for a proper taxonomic assessment (Routtu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations